NTDs V.2.0: "blue marble health"--neglected tropical disease control and elimination in a shifting health policy landscape. - Peter J Hotez (Public Library of Science (PLoS), 2013)
The concept of the neglected tropical diseases (NTDs) was established in the aftermath of the Millennium Development Goals. Here, we summarize the emergence of several new post-2010 global health documents and policies, and how they may alter the way we frame the world's major NTDs since they were first highlighted. These documents include a new Global Burden of Disease 2010 Study that identifies visceral leishmaniasis and food-borne trematode infections as priority diseases beyond the seven NTDs originally targeted by preventive chemotherapy, a London Declaration for access to essential medicines, and a 2013 World Health Assembly resolution on NTDs. Additional information highlights an emerging dengue fever pandemic. New United Nations resolutions on women and the non-communicable diseases (NCDs) have not yet embraced NTDs, which may actually be the most common afflictions of girls and women and represent a stealth cause of NCDs. NTDs also have important direct and collateral effects on HIV/AIDS and malaria, and there is now a robust evidence base and rationale for incorporating NTDs into the Global Fund to Fight AIDS, Tuberculosis, and Malaria. "Blue marble health" is an added concept that recognizes a paradoxical NTD disease burden among the poor living in G20 (Group of Twenty) and other wealthy countries, requiring these nations to take greater ownership for both disease control and research and development. As we advance past the year 2015, it will be essential to incorporate global NTD elimination into newly proposed Sustainable Development Goals.